Human Pancreas Procurement and Processing of Prodo Laboratories v1 - Giray Eryilmaz (2024)
Human pancreas procurement and processing as described in Advances in Human Islet Processing: Manufacturing Steps to Achieve Predictable Islet Outcomes from Research Pancreases David W. Scharp, Jayagowri Arulmoli, Kelly Morgan, Hannah Sunshine, Ergeng HaoReceived: October 15, 2018; Published: February 26, 2019; doi:10.21926/obm.transplant.1901052